Preparation method of flow battery electrode based on tree xylem conduit and globefish skin bionics
Through the preparation method of liquid flow electrodes for tree xylem and pufferfish skin bionic, the problems of flow battery activation loss and poor electrochemical activity are solved, the specific surface area and electrochemical performance of the electrode are improved, and high-efficiency energy conversion and stability are achieved. It has low cost and environmental protection advantages.
Patent Information
- Application Number
- CN202411130611.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2025-01-03
AI Technical Summary
Existing flow batteries have problems of activation loss and poor electrochemical activity, which affect their performance and life.
The preparation method of liquid flow electrode based on tree xylem catheter and pufferfish skin bionics is adopted. The specific surface area and electrochemical performance of the electrode are enhanced by heating and nitrogen doping treatment, and non-metallic layered semiconductor black phosphorus nanosheets, gelatin, hexahydrate nitric acid The mixed solution of zinc, zinc oxide and other materials is modified by electrodes to enhance the pore structure and the transport capacity of active substances.
It significantly improves the specific surface area, electrochemical reaction activity and stability of the electrode, improves the energy conversion efficiency and charge and discharge capacity retention rate, reduces costs, and effectively utilizes construction waste, realizing the preparation of high-performance electrode materials.
Smart Images

Figure CN119252947A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to liquid flow battery energy storage technology, and in particular to a liquid flow battery electrode based on tree xylem vessels and pufferfish skin bionics. Background Art
[0002] Electrochemical energy storage technology has the advantages of high performance, long cycle, cleanness, and high compatibility with renewable energy. Combining renewable energy with electrochemical energy storage technology is an inevitable choice to maintain energy demand. Redox flow batteries have been widely recognized in large-scale energy storage applications due to their advantages such as power and energy density decoupling, long cycle life, scalability, depth of discharge, cost-effectiveness and easy manufacturing.
[0003] At present, liquid flow batteries have disadvantages such as activation loss and poor electrochemical activity. Electrode materials are important elements that affect the performance of liquid flow batteries. The treatment of carbon-based electrodes is an important method to improve the electrochemical performance of liquid flow batteries. Physical and chemical treatment of electrodes, pore regulation, and atomic doping are common methods to improve the performance of electrodes.
[0004] During the electrochemical reaction at the electrode, the pores can provide a place for the electrochemical reaction to occur and for the material to be transported. Porosity and a large surface area can provide more reactive sites and greater reactive activity. In nature, the xylem of tree materials is a natural porous channel material for transporting water and inorganic salts. In addition, pufferfish swell their bodies into spiny balls by swallowing water or air. Benefiting from these two bionic ideas, electrodes treated with xylem are constructed, and the swollen active substances are transported to the surface of the electrode pores through pufferfish-like materials and the pores are regulated to greatly enhance the electrochemical reaction activity. No relevant research has been found so far. This new idea of electrode treatment can treat building material waste and turn waste into treasure while obtaining high-performance electrode materials, which has great economic and environmental benefits. Summary of the invention
[0005] In order to overcome the deficiencies in the prior art, the present invention provides a method for preparing a flow battery electrode based on tree xylem vessels and pufferfish skin bionics.
[0006] In order to overcome the problems in the prior art, the present application provides a flow battery electrode based on tree xylem vessels and pufferfish skin bionics.
[0007] The present invention provides a method for preparing a flow battery electrode based on tree xylem vessels and pufferfish skin bionics, which comprises the following steps:
[0008] (1) Preparation of xylem electrodes: Select the xylem of a tree, heat and keep it warm in an air atmosphere, and then calcine it at high temperature in a nitrogen atmosphere to obtain a preliminary xylem electrode;
[0009] (2) Electrode modification: The xylem electrode was immersed in an ethanol solution of ammonium nitrate and sodium nitrate, dried and calcined to obtain a nitrogen-doped electrode;
[0010] (3) Electrode modification and enhancement: prepare a mixed solution of non-metallic layered semiconductor black phosphorus nanosheets, gelatin, zinc nitrate hexahydrate, zinc oxide and hexadecyltrimethoxysilane, immerse the electrode sheet obtained in step (2) in the solution, remove the gelatin template and dry it.
[0011] Preferably, in step (1), a small piece of woody body of a tree is first placed in an air atmosphere and heated to 260-280°C and maintained for 4-5 hours, with a heating rate of 8-10°C / min. After cooling to room temperature, the small piece of woody body is taken out and then placed in a vacuum tube furnace in a nitrogen atmosphere and maintained at 800-850°C for 3-4 hours, with a heating rate of 16-18°C / min.
[0012] Preferably, the ethanol solution of ammonium nitrate and sodium nitrate has a mass ratio of ammonium nitrate to sodium nitrate of 3:1 to 4:1, and is dissolved in a 65% to 75% ethanol solution.
[0013] Preferably, in step (2), the calcination after drying is carried out in a vacuum tube furnace in a nitrogen atmosphere at 850-900° C. for 3-4 hours, and the heating rate of the vacuum tube furnace is 16-18° C. / min.
[0014] Preferably, in step (3), the mixed solution is prepared by adding 0.16-0.24 g of zinc nitrate hexahydrate, 0.11-0.13 g of zinc oxide and 2.5-3.1 ml of hexadecyltrimethoxysilane to 100-120 mL of a 30-40 w / v% gelatin solution containing 0.1 mg / mL of non-metallic layered semiconductor black phosphorus nanosheets, and heating to 48-52° C. and maintaining the mixture for 3-4 hours under magnetic stirring at 120-150 rpm.
[0015] Preferably, in step (3), the obtained electrode sheet is immersed in the solution for 2 to 3 hours and cooled to room temperature, and the solidified electrode sheet is placed in an air atmosphere and heated to 70 to 80° C. and maintained for 4 to 5 hours to remove the gelatin template and dry for later use.
[0016] Select commercially available fir wood blocks or elm wood blocks and cut them into small blocks with a thickness of 3 to 3.2 mm and equal length and width of 9.5 to 10.5 cm. Place the small block of tree xylem in an air atmosphere and heat it to 260 to 280°C and maintain it for 4 to 5 hours, with a heating rate of 8 to 10°C / min. Take out the small block of xylem after cooling to room temperature. Place the small block in a vacuum tube furnace in a nitrogen atmosphere and maintain it at 800 to 850°C for 3 to 4 hours, with a heating rate of 16 to 18°C / min. Take it out after cooling to room temperature to obtain a preliminary xylem electrode. Immerse the small block in a concentrated nitric acid solution at 75 to 85°C for 2.5 to 3 hours to adjust the wettability and electrochemical properties. After nitric acid treatment, the specific surface area increases from 406.9 to 436.2 m 2 / g increased to 446.5~461.0m 2 / g, the electrode energy conversion efficiency is increased from 72.6-74.1% to 75.1-76.3%, and more than 99% of impurities are removed by concentrated nitric acid. Then take out the small pieces, wash them with deionized water until the pH is higher than 6.5 and dry them for use. Due to the problems of impurities, stability and corrosion resistance, the electrode needs to be treated as follows.
[0017] Cut the above electrode into small pieces of 3cm×3cm×1.4mm. Dissolve 20.5-21.5g (mass ratio of 3:1-4:1) of a mixture of ammonium nitrate and sodium nitrate in a 65%-75% ethanol solution. Immerse the electrode sheet in the solution for 1.5-2h. After taking out the electrode sheet, dry it at 60℃ for 8-10h, and then cool it to room temperature. Place the small piece in a vacuum tube furnace in a nitrogen atmosphere and keep it at 850-900℃ for 3-4h. The heating rate of the vacuum tube furnace is 16-18℃ / min. After cooling to room temperature, take it out to obtain a modified xylem piece. This electrode is a nitrogen-doped electrode. After nitrogen doping, the specific surface area increases from 446.5 to 461.0m 2 / g increased to 472.3~492.8m 2 / g, the electrode energy conversion efficiency increased from 75.1-76.3% to 76.5-77.8%, and the chemical properties and stability were improved to a certain extent.
[0018] 0.16-0.24 g of zinc nitrate hexahydrate, 0.11-0.13 g of zinc oxide and 2.5-3.1 ml of hexadecyltrimethoxysilane were added to 100-120 mL of a 30-40 w / v% gelatin solution containing 0.1 mg / mL of non-metallic layered semiconductor black phosphorus nanosheets, and heated to 48-52°C and maintained for 3-4 hours under magnetic stirring at 120-150 rpm. Then, the stirring was stopped and the obtained electrode sheet was immersed in the solution for 2-3 hours and cooled to room temperature. The cured electrode sheet was placed in an air atmosphere and heated to 70-80°C and maintained for 4-5 hours to remove the gelatin template and dried for use. The electrode was treated by adjusting the pore size and treating the pore surface, and the specific surface area increased from 472.3 to 492.8 m 2 / g increased to 612.8~644.6m 2 / g, the electrode energy conversion efficiency increased from 76.5-77.8% to 85.4-86.6%. The battery's charge and discharge capacity retention rate increased by more than 20% to 85.5%, greatly improving the pore characteristics, corrosion resistance and electrochemical performance.
[0019] The above-mentioned flow battery electrode is used as the working electrode, the platinum electrode is used as the counter electrode, and Ag / AgCl is used as the reference electrode to form a three-electrode system of an all-vanadium flow battery. The ion exchange membrane is Nafion 212. The electrolyte is 0.1M VOSO4 and 2.0MH2SO4. Benefiting from the bionic idea of plant xylem, an electrode with vertically arranged channels and porous structure is created. In addition, it benefits from the bionic idea of pufferfish skin contraction and relaxation: the active substance is sent into the pore channel in the contracted state, and the expanded active substance is transported to the pore surface for contact through the expansion effect. While adding active substances, the pore size can be expanded to increase the specific surface area, similar to the pufferfish swelling and thinning of the skin, and the contraction and relaxation of the material are used to achieve a similar physiological process to the pufferfish. The electrode pore size is further increased, the electrode specific surface area is expanded, and the electrode modification material is further extended to the surface of the pore, which improves the corrosion resistance and electrochemical performance.
[0020] The present invention also provides a flow battery electrode prepared by the above method based on tree xylem vessels and pufferfish skin bionics.
[0021] The beneficial effects of the present invention are as follows:
[0022] The present invention organically integrates two bionic ideas into the electrode design. In nature, the xylem of tree materials is a natural porous channel material for transporting water and inorganic salts. In addition, pufferfish swell their bodies into prickly spheres by swallowing water or air. Benefiting from these two bionic ideas, electrodes treated with xylem are constructed, and the swollen active substances are transported to the electrode pore surface through pufferfish-like materials and the pores are regulated to greatly enhance the electrochemical reaction activity. No relevant research has been found so far. This new idea of electrode treatment can process building material waste and turn waste into treasure while obtaining high-performance electrode materials, which has great economic and environmental social benefits.
[0023] The specific surface area of the electrode designed according to the bionics idea (612.8~644.6m 2 / g) compared with the original electrode specific surface area (354.7~388.3m 2 / g) is greatly improved. Due to the pore size control and surface treatment, the electrode stability, activity and electronic conduction characteristics are correspondingly improved. In addition to providing abundant electrochemical reaction sites, the reduced Zeta overpotential provides an additional driving force for the adsorption of vanadium ions on the electrode surface. The xylem electrode has the advantages of low cost, high efficiency, good stability and effective use of construction waste. After testing, the electrode in the present invention has a current density of 100mA / cm 2 Compared with the original carbon electrode, the energy conversion efficiency of the electrode increased from 70.3-74.2% to 85.4-86.6%, and the maximum energy density increased from 296mW / cm 2 Increased to 372mW / cm 2 . In addition, after 150 cycles, the battery's charge and discharge capacity retention rate can be increased from 59.6% to 85.5%, reflecting the extremely high electrochemical properties of the electrode. The three more important factors in the present invention are the electrode preparation temperature, whether the electrode has been modified, and the application ratio of each chemical in the electrode modification: if the preparation temperature is low, it cannot be completely carbonized, and if it is too high, it will lead to performance degradation; after nitrogen doping modification, the performance is greatly improved. Without this step, the specific surface area and electrochemical performance will be reduced; in addition, the application ratio of each chemical in the electrode modification is mainly the amount of black phosphorus nanosheets added. When the amount added is small, this step is of little significance. When the amount added exceeds the scope of the present invention, it has little effect on the final performance, but the cost is greatly increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1The figure is a schematic diagram of the electrode preparation process of the present invention. 1 is the cross-sectional structure of the vessel pores of the prepared electrode after step (1), 2 is a schematic diagram of the xylem structure treated by carbonization, 3 is a schematic diagram of the pore surface after electrode modification in step (2), and 4 is a schematic diagram of pore diameter adjustment and pore surface treatment after electrode modification and enhancement in step (3). After the expansion effect, the pore diameter becomes larger, and the specific surface area becomes larger accordingly.
[0025] Figure 2 The microscopic pictures of the vertically arranged channels and porous structures of the electrode preparation product of Example 1 of the present invention are as follows: (a) is the cross-sectional structure of the catheter pores after the electrode modification and enhancement in step (3), and the pore diameters are mostly concentrated in the range of 5 to 15 μm. (b) is the longitudinal section structure of the fibers after the electrode modification and enhancement in step (3).
[0026] Figure 3 This is a comparison chart of the efficiency of the electrode of Example 1 of the present invention and the existing carbon electrode. Compared with the original carbon electrode, the energy conversion efficiency of this electrode is increased from 70.3 to 85.4.
[0027] Figure 4 This is a comparison chart of the cycle performance of the electrode of Example 1 of the present invention and the existing carbon electrode. After 150 cycles, the charge and discharge capacity retention rate of the battery increased from 59.6% to 85.5%, reflecting the high electrochemical characteristics of the electrode.
[0028] Figure 5 It is a technical roadmap of the method described in the present invention. DETAILED DESCRIPTION
[0029] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present application will be further described below in conjunction with specific embodiments.
[0030] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present application will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0031] The fir wood blocks or elm wood blocks used in the present invention are from commercial products or building material waste. Concentrated nitric acid, ammonium nitrate, sodium nitrate, ethanol, black phosphorus nanosheets, gelatin, zinc nitrate hexahydrate, zinc oxide, hexadecyltrimethoxysilane, manganese dioxide, sulfuric acid and vanadyl sulfate (IV) hydrate are from Sinopharm Group.
[0032] Example 1
[0033] (1) Preparation of xylem electrodes. Commercially available fir wood blocks or elm wood blocks were selected and cut into small blocks with a thickness of 3.1 mm, equal length and width, and 10 cm. The small blocks of tree xylem were placed in an air atmosphere and heated to 270°C and maintained for 4.5 h, with a heating rate of 9°C / min. After cooling to room temperature, the small blocks were taken out. The small blocks were placed in a vacuum tube furnace in a nitrogen atmosphere and maintained at 825°C for 3.5 h, with a heating rate of 17°C / min. After cooling to room temperature, they were taken out to obtain a preliminary xylem electrode. The small blocks were immersed in a concentrated nitric acid solution at 80°C for 2.75 h to adjust the wettability and electrochemical properties. After that, the small blocks were taken out, washed with deionized water until the pH was higher than 6.5, and dried for use. Due to problems with impurities, stability, and corrosion resistance, the electrode needs to be treated as follows.
[0034] (2) Electrode modification. Cut the above electrode into small pieces of 3cm×3cm×1.4mm. Dissolve 21g of a mixture of ammonium nitrate and sodium nitrate (mass ratio of 3.5:1) in 70% ethanol solution. Immerse the electrode piece in the solution for 1.75h. After taking out the electrode piece, dry it at 60℃ for 9h, and then cool it to room temperature. Place the small piece in a vacuum tube furnace in a nitrogen atmosphere and keep it at 875℃ for 3.5h. The heating rate of the vacuum tube furnace is 17℃ / min. After cooling to room temperature, take it out to obtain a modified xylem piece. This electrode is a nitrogen-doped electrode, and its chemical properties and stability have been improved to a certain extent.
[0035] (3) Electrode modification and enhancement. Add 0.2 g zinc nitrate hexahydrate, 0.12 g zinc oxide and 2.8 ml hexadecyltrimethoxysilane to 110 mL of a 35 w / v% gelatin solution containing 0.1 mg / mL non-metallic layered semiconductor black phosphorus nanosheets. Heat to 50°C and maintain for 3.5 h under magnetic stirring at 135 rpm. Then stop stirring and immerse the electrode sheet obtained in step (2) in the solution for 2.5 h and cool to room temperature. Place the cured electrode sheet in an air atmosphere, heat to 75°C and maintain for 4.5 h to remove the gelatin template and dry for use. The electrode greatly improves the pore characteristics, corrosion resistance and electrochemical performance through pore size adjustment and pore surface treatment.
[0036] (4) Electrode use. The liquid flow battery electrode obtained in step (3) is used as the working electrode, the platinum electrode is used as the counter electrode, and Ag / AgCl is used as the reference electrode to form a three-electrode system of an all-vanadium liquid flow battery. The ion exchange membrane is Nafion 212. The electrolyte is 0.1M VOSO4 and 2.0M H2SO4. Benefiting from the bionic idea of plant xylem, an electrode with vertically arranged channels and a porous structure is created. In addition, benefiting from the bionic idea of pufferfish skin contraction and relaxation, the electrode pore size is further increased, the electrode specific surface area is expanded, and the electrode modification material is further extended to the surface of the pores, thereby improving the corrosion resistance and electrochemical performance. The two bionic ideas are coupled in the electrode design. The specific surface area of the electrode (630.2m 2 / g) compared with the original electrode (original carbon electrode without any treatment) specific surface area (367.5m 2 / g) is greatly improved, providing abundant electrochemical reaction sites, and the reduced Zeta overpotential provides additional driving force for the adsorption of vanadium ions on the electrode surface. The xylem electrode has the advantages of low cost, high efficiency, good stability and effective use of construction waste. After testing, the electrode in the present invention has a current density of 100mA / cm 2 Compared with the original carbon electrode, the energy conversion efficiency of this electrode increased from 72.3% to 85.8%, and the maximum energy density increased from 296mW / cm 2 Increased to 372mW / cm 2 In addition, after 150 cycles, the battery's charge and discharge capacity retention rate increased from 59.6% to 85.5%, reflecting the extremely high electrochemical properties of the electrode.
[0037] Example 2
[0038] (1) Preparation of xylem electrodes. Commercially available fir wood blocks or elm wood blocks were selected and cut into small blocks with a thickness of 3 mm and equal length and width of 9.5 cm. The small blocks of tree xylem were placed in an air atmosphere and heated to 280°C and maintained for 4 hours at a heating rate of 10°C / min. After cooling to room temperature, the small blocks were taken out. The small blocks were placed in a vacuum tube furnace in a nitrogen atmosphere and maintained at 800°C for 4 hours at a heating rate of 16°C / min. After cooling to room temperature, they were taken out to obtain a preliminary xylem electrode. The small blocks were immersed in a concentrated nitric acid solution at 75°C for 3 hours to adjust the wettability and electrochemical properties. After that, the small blocks were taken out, washed with deionized water until the pH was higher than 6.5 and dried for use. Due to problems with impurities, stability and corrosion resistance, the electrode needs to be treated as follows.
[0039] (2) Electrode modification. Cut the above electrode into small pieces of 3cm×3cm×1.4mm. Dissolve 20.5g of a mixture of ammonium nitrate and sodium nitrate (mass ratio of 4:1) in a 65% ethanol solution. Immerse the electrode piece in the solution for 2h. After taking out the electrode piece, dry it at 60℃ for 8h, and then cool it to room temperature. Place the small piece in a vacuum tube furnace in a nitrogen atmosphere and keep it at 900℃ for 3h. The heating rate of the vacuum tube furnace is 18℃ / min. After cooling to room temperature, take it out to obtain a modified xylem piece. This electrode is a nitrogen-doped electrode, and its chemical properties and stability have been improved to a certain extent.
[0040] (3) Electrode modification and enhancement. Add 0.16g zinc nitrate hexahydrate, 0.13g zinc oxide and 2.5ml hexadecyltrimethoxysilane to 100mL of a 40w / v% gelatin solution containing 0.1mg / mL non-metallic layered semiconductor black phosphorus nanosheets. Heat to 52°C and maintain for 3h under magnetic stirring at 120rpm. Then stop stirring and immerse the electrode sheet obtained in step (2) in the solution for 3h and cool to room temperature. Place the cured electrode sheet in an air atmosphere, heat to 70°C and maintain for 5h to remove the gelatin template and dry for use. The electrode greatly improves the pore characteristics, corrosion resistance and electrochemical performance through pore size adjustment and pore surface treatment.
[0041] (4) Electrode use. The liquid flow battery electrode obtained in step (3) is used as the working electrode, the platinum electrode is used as the counter electrode, and Ag / AgCl is used as the reference electrode to form a three-electrode system of an all-vanadium liquid flow battery. The ion exchange membrane is Nafion 212. The electrolyte is 0.1M VOSO4 and 2.0M H2SO4. Benefiting from the bionic idea of plant xylem, an electrode with vertically arranged channels and a porous structure is created. In addition, benefiting from the bionic idea of pufferfish skin contraction and relaxation, the electrode pore size is further increased, the electrode specific surface area is expanded, and the electrode modification material is further extended to the surface of the pores, thereby improving the corrosion resistance and electrochemical performance. The two bionic ideas are coupled in the electrode design. The specific surface area of the electrode (612.8m 2 / g) compared with the original electrode specific surface area (354.7m 2 / g) is greatly improved, providing abundant electrochemical reaction sites, and the reduced Zeta overpotential provides additional driving force for the adsorption of vanadium ions on the electrode surface. The xylem electrode has the advantages of low cost, high efficiency, good stability and effective use of construction waste. After testing, the electrode in the present invention has a current density of 100mA / cm 2 When compared with the original carbon electrode, the energy conversion efficiency of this electrode was increased from 70.3% to 85.4%.
[0042] Example 3
[0043] (1) Preparation of xylem electrodes. Commercially available fir wood blocks or elm wood blocks were selected and cut into small blocks with a thickness of 3.2 mm and equal length and width of 10.5 cm. The small blocks of tree xylem were placed in an air atmosphere and heated to 260°C and maintained for 5 h, with a heating rate of 8°C / min. After cooling to room temperature, the small blocks of xylem were taken out. The small blocks were placed in a vacuum tube furnace in a nitrogen atmosphere and maintained at 850°C for 3 h, with a heating rate of 18°C / min. After cooling to room temperature, they were taken out to obtain a preliminary xylem electrode. The small blocks were immersed in a concentrated nitric acid solution at 85°C for 2.5 h to adjust the wettability and electrochemical properties. After that, the small blocks were taken out, washed with deionized water until the pH was higher than 6.5, and dried for use. Due to problems with impurities, stability and corrosion resistance, the electrode needs to be treated as follows.
[0044] (2) Electrode modification. Cut the above electrode into small pieces of 3cm×3cm×1.4mm. Dissolve 21.5g of a mixture of ammonium nitrate and sodium nitrate (mass ratio is 3:1) in 75% ethanol solution. Immerse the electrode piece in the solution for 1.5h. After taking out the electrode piece, dry it at 60℃ for 10h, and then cool it to room temperature. Place the small piece in a vacuum tube furnace in a nitrogen atmosphere and keep it at 850℃ for 4h. The heating rate of the vacuum tube furnace is 16℃ / min. After cooling to room temperature, take it out to obtain a modified xylem piece. This electrode is a nitrogen-doped electrode, and its chemical properties and stability have been improved to a certain extent.
[0045] (3) Electrode modification and enhancement. Add 0.24 g zinc nitrate hexahydrate, 0.11 g zinc oxide and 3.1 ml hexadecyltrimethoxysilane to 120 mL of a 30 w / v% gelatin solution containing 0.1 mg / mL non-metallic layered semiconductor black phosphorus nanosheets. Heat to 48°C and maintain for 4 hours under magnetic stirring at 150 rpm. Then stop stirring and immerse the electrode sheet obtained in step (2) in the solution for 2 hours and cool to room temperature. Place the cured electrode sheet in an air atmosphere, heat to 80°C and maintain for 4 hours to remove the gelatin template and dry for use. The electrode greatly improves the pore characteristics, corrosion resistance and electrochemical performance through pore size adjustment and pore surface treatment.
[0046] (4) Electrode use. The liquid flow battery electrode obtained in step (3) is used as the working electrode, the platinum electrode is used as the counter electrode, and Ag / AgCl is used as the reference electrode to form a three-electrode system of an all-vanadium liquid flow battery. The ion exchange membrane is Nafion 212. The electrolyte is 0.1M VOSO4 and 2.0M H2SO4. Benefiting from the bionic idea of plant xylem, an electrode with vertically arranged channels and a porous structure is created. In addition, benefiting from the bionic idea of pufferfish skin contraction and relaxation, the electrode pore size is further increased, the electrode specific surface area is expanded, and the electrode modification material is further extended to the surface of the pores, thereby improving the corrosion resistance and electrochemical performance. Two bionic ideas are coupled in the electrode design. The specific surface area of the electrode (644.6m 2 / g) compared with the original electrode specific surface area (388.3m 2 / g) is greatly improved, providing abundant electrochemical reaction sites, and the reduced Zeta overpotential provides additional driving force for the adsorption of vanadium ions on the electrode surface. The xylem electrode has the advantages of low cost, high efficiency, good stability and effective use of construction waste. After testing, the electrode in the present invention has a current density of 100mA / cm 2 When compared with the original carbon electrode, the energy conversion efficiency of this electrode was increased from 74.2% to 86.6%.
[0047] In the present invention, the electrode is at a current density of 100 mA / cm 2 Compared with the original carbon electrode, the energy conversion efficiency of the electrode increased from 70.3-74.2% to 85.4-86.6%, and the maximum energy density increased from 296mW / cm 2 Increased to 372mW / cm 2 . In addition, after 150 cycles, the battery's charge and discharge capacity retention rate can be increased from 59.6% to 85.5%, reflecting the extremely high electrochemical properties of the electrode. The three more important factors in the present invention are the electrode preparation temperature, whether the electrode has been modified, and the application ratio of each chemical in the electrode modification: if the preparation temperature is low, it cannot be completely carbonized, and if it is too high, it will lead to performance degradation; after nitrogen doping modification, the performance is greatly improved. Without this step, the specific surface area and electrochemical performance will be reduced; in addition, the application ratio of each chemical in the electrode modification is mainly the amount of black phosphorus nanosheets added. When the amount added is small, this step is of little significance. When the amount added exceeds the scope of the present invention, it has little effect on the final performance, but the cost is greatly increased.
[0048] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a flow battery electrode based on tree xylem vessels and pufferfish skin bionics, characterized in that: The following steps are included: (1) Preparation of xylem electrodes: Select the xylem of a tree, heat and keep it warm in an air atmosphere, and then calcine it at high temperature in a nitrogen atmosphere to obtain a preliminary xylem electrode; (2) Electrode modification: The xylem electrode was immersed in an ethanol solution of ammonium nitrate and sodium nitrate, dried and calcined to obtain a nitrogen-doped electrode; (3) Electrode modification and enhancement: prepare a mixed solution of non-metallic layered semiconductor black phosphorus nanosheets, gelatin, zinc nitrate hexahydrate, zinc oxide and hexadecyltrimethoxysilane, immerse the electrode sheet obtained in step (2) in the solution, remove the gelatin template and dry it.
2. The method for preparing a flow battery electrode based on tree xylem vessels and pufferfish skin bionics according to claim 1, characterized in that: In step (1), a small piece of woody body of a tree is first placed in an air atmosphere and heated to 260-280°C and maintained for 4-5 hours, with a heating rate of 8-10°C / min. After cooling to room temperature, the small piece of woody body is taken out and then placed in a vacuum tube furnace in a nitrogen atmosphere and maintained at 800-850°C for 3-4 hours, with a heating rate of 16-18°C / min.
3. The method for preparing a flow battery electrode based on tree xylem vessels and pufferfish skin bionics according to claim 1, characterized in that: The ammonium nitrate and sodium nitrate ethanol solution has a mass ratio of ammonium nitrate to sodium nitrate of 3:1 to 4:1 and is dissolved in a 65% to 75% ethanol solution.
4. The method for preparing a flow battery electrode based on tree xylem vessels and pufferfish skin bionics according to claim 3, characterized in that: In step (2), the calcination after drying is carried out in a vacuum tube furnace in a nitrogen atmosphere at 850-900° C. for 3-4 hours, and the heating rate of the vacuum tube furnace is 16-18° C. / min.
5. The method for preparing a flow battery electrode based on tree xylem vessels and pufferfish skin bionics according to claim 1, characterized in that: In step (3), the mixed solution is prepared by adding 0.16-0.24 g of zinc nitrate hexahydrate, 0.11-0.13 g of zinc oxide and 2.5-3.1 ml of hexadecyltrimethoxysilane to 100-120 mL of a 30-40 w / v% gelatin solution containing 0.1 mg / mL of non-metallic layered semiconductor black phosphorus nanosheets, and heating the mixture to 48-52° C. and maintaining the mixture for 3-4 hours under magnetic stirring at 120-150 rpm.
6. The method for preparing a flow battery electrode based on tree xylem vessels and pufferfish skin bionics according to claim 5, characterized in that: In step (3), the obtained electrode sheet is immersed in the solution for 2 to 3 hours and cooled to room temperature. The solidified electrode sheet is placed in an air atmosphere and heated to 70 to 80° C. and maintained for 4 to 5 hours to remove the gelatin template and dry for later use.
7. A flow battery electrode based on tree xylem vessels and pufferfish skin bionics prepared by the method according to any one of claims 1 to 6.
